USE OF HIGH-STRENGTH BAINITIC CAST IRON FOR PRODUCING GEAR WHEELS - A. I. Pokrovskiy; L. R. Dudetskaya (Литьë и металлургия, 2015)
The advantages and drawbacks of high-strength cast irons with bainitic structure are reviewed basing on the authors’ own experience in the production of critical partsfrom this material and on the analysis of world trends. A possibility of the replacement of alloy steels by bainitic cast iron in manufacturing critical machine parts is discussed.